Current status, and future prospects of pharmaco-epidemiology and post-marketing surveillance in Saudi Arabia: A review of literature - Ashraf El-Metwally (Elsevier, 2018)
Background: Pharmacoepidemiology is the concept used for evaluating the impact of drugs among a large number of people in the post-marketing phase. The use of this concept makes it increasingly necessary to detect the recurrence of drug-related anomalies that mostly occur through health care professionals or patients themselves. Pharmacoepidemiology is important since it helps to provide the right balance of benefits versus risks of the drug products while remaining an excellent tool to prepare the risk/benefit balance profile. Aim: The objective of this study is to review and explore the current status and future prospects of pharmacoepidemiology and post-marketing surveillance in Saudi Arabia. Methods: A literature review has been conducted using keywords such as pharmacoepidemiology'; 'post-marketing'; 'surveillance'; 'Saudi Arabia'; 'ADRs'; and 'pharmacovigilance'. The study refines its focus on 13 pharmacoepidemiology and post-marketing surveillance research studies conducted in Saudi Arabia using the databases; Embase, PubMed, EBSCOhost, MEDLINE, and AMED. Results: Pharmacoepidemiology and post-marketing surveillance creates a body of research in Saudi Arabia, but within a restricted scope. The studies that were reviewed assessed the challenge from various perspectives. Lack of knowledge, post-marketing surveillance, ADR reporting, and increased use of generic products were reported. Conclusion: The current level of research may be widened and increased through improving the process of ADRs reporting system. More research needs to be conducted based on nation-wide observational studies. Collaboration among medical professionals, academics and industries should continue to establish a more efficient and consistent post-marketing surveillance system. Keywords: Pharmacoepidemiology, Post-marketing surveillance, Saudi Arabia, Pharmacovigilance, ADRs